At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

please help with this question, thank you!!​

Please Help With This Question Thank You class=

Sagot :

Answer:

[tex]-\sqrt{2}[/tex]

Step-by-step explanation:

Note that:

[tex]a^2-2ab+b^2=(a-b)^2 = 4ab \\ \\ a^2 + 2ab+b^2 = (a+b)^2 = 8ab \\ \\ \implies \frac{a+b}{a-b}=\frac{\sqrt{8ab}}{-\sqrt{4ab}}=-\sqrt{2}[/tex]

Answer:

[tex]\sf \dfrac{a+b}{a-b}= -\sqrt{2}[/tex]

Step-by-step explanation:

[tex]\sf a^2 + b^2 = 6ab \qquad where\:\:0 < a < b[/tex]

Basic formula:

[tex]\sf (a + b)^2 = a^2 +b^2 +2ab[/tex]

[tex]\sf (a - b)^2 = a^2 + b^2 -2ab[/tex]

solve for a + b

[tex]\sf \rightarrow a^2 + b^2 = 6ab[/tex]

[tex]\sf \rightarrow (a+b)^2-2ab = 6ab[/tex]

[tex]\sf \rightarrow (a+b)^2 = 6ab+2ab[/tex]

[tex]\sf \rightarrow (a+b)^2 = 8ab[/tex]

[tex]\sf \rightarrow a+b = \pm \sqrt{8ab}[/tex]

solve for a - b

[tex]\sf \rightarrow a^2 + b^2 = 6ab[/tex]

[tex]\sf \rightarrow (a-b)^2 + 2ab = 6ab[/tex]

[tex]\sf \rightarrow (a-b)^2 = 6ab-2ab[/tex]

[tex]\sf \rightarrow (a-b)^2 = 4ab[/tex]

[tex]\sf \rightarrow a-b = \pm \sqrt{4ab}[/tex]

Now solve for (a + b)/(a - b)

[tex]\sf \rightarrow \dfrac{a+b}{a-b}= \dfrac{\pm\sqrt{8ab} }{\pm\sqrt{4ab} }[/tex]

[tex]\sf \rightarrow \dfrac{a+b}{a-b}= \pm \sqrt\dfrac{8ab }{4ab}[/tex]

[tex]\sf \rightarrow \dfrac{a+b}{a-b}= \pm \sqrt{2}[/tex]

As, the value of b is greater than the value of a and both the values a  and b are greater than 0. It turns the value of expression negative as the denominator will be always evaluated to negative integer and the numerator value always > 0. So, the answer will be negative, -√2.

[tex]\sf \rightarrow \dfrac{a+b}{a-b}= - \sqrt{2}[/tex]